Anthropometric, physical activity, and psychological characteristics of Korean adults with and without developmental coordination disorder (DCD) - Kim, Min Joo; Nam, Soo Mi; Kim, Byeol; Park, Ilhyeok; Park, Jaebum; Shim, Jae Kun (Frontiers in Human Neuroscience, 2023)
Developmental Coordination Disorder (DCD), also known as Dyspraxia, is characterized by movement difficulties in individuals without discernible neurological disorders or identifiable medical conditions. Previous studies from various countries have highlighted disparities in anthropometric, physical activity, and psychological characteristics between children diagnosed with DCD and their typically developing (TD) peers. These differences are influenced by sociocultural norms and geographical locations. However, little attention has been given to scrutinizing analogous differences in adult populations, particularly within Korea. This study aims to address this knowledge gap by employing a battery of questionnaires to assess anthropometric, physical activity, and psychological traits in a cohort of 377 Korean adults, encompassing those with DCD (n=54) alongside TD counterparts (n=323). It was hypothesized that Korean adults with DCD would exhibit higher body mass index and lower ratings in physical activity and psychological characteristics than TD, consistent with the previous studies performed in other countries on children. The results showed no statistically significant differences between the DCD and TD groups in anthropometric characteristics such as weight, height, body mass index, and perceived difficulties in fine motor skills. The prevalence of walking and biking for daily commuting and the customary use of chopsticks in daily routines within Korean society might have contributed to the mitigation of anthropometric and fine motor skill limitations among individuals with DCD. Statistically significant differences were found in physical activity levels at work and recreational settings, as shown in physical activity scores and duration. The DCD group also displayed lower scores across several psychological characteristics, including exercise adherence, intrinsic motivation, self-efficacy, physical self-concept, exercise expectations, and intrinsic regulation. These findings underscore the necessity of incorporating sociocultural dynamics when investigating anthropometric, physical activity, and psychological characteristics in adults with DCD. Future research studies are warranted to elucidate the underlying mechanisms driving the observed patterns